Analysis of Financial Regulatory Challenges for the Development of Islamic Banking in Indonesia - Panjaitan, Nana Karlina; Nurbaiti, Nurbaiti; Daulay, Aqwa Naser (Borong Newinera Publisher, 2024)
This article aims to present an analysis of the regulatory challenges in Islamic banking supervision on the sustainability of business and financial models, with a case study on Bank Syariah Indonesia (BSI). In the context of the growth of the Islamic banking industry in Indonesia, the main question raised is how regulation affects the sustainability of the business and financial models of Islamic banks, particularly BSI. This research uses a qualitative approach by analyzing relevant laws and regulations and a case study of BSI. The results show that complex and constantly changing regulations can be an obstacle to the sustainability of Islamic banks' business and financial models. Although BSI has adapted itself to the changes, challenges remain, especially in terms of meeting capital requirements, product diversification, and enforcement of sharia rules. In answering the research question, the author concludes that to achieve optimal sustainability, regulations need to be adjusted to better support the development of the Islamic banking industry, including providing incentives for innovation and consistent fulfillment of sharia principles.